PENGARUH PENGALAMAN DAN PRODUKTIVITAS KERJA TERHADAP PENDAPATAN PENGRAJIN KAIN TENUN (Studi Pada Kelompok Tenun Kemang Langit Kecamatan Moyo Hilir) - A Asmini; K Kamaruddin; Furna Aprianti (Fakultas Ekonomi dan Manajemen, 2022)
The purpose of this study was to know the influence of work experirnce and productivity toward the income of woven cloth craftsmen in the Kemang Langit Group at Moyo Hilir Sub-District, both partially and simultaneously. Type of this study was quantitative associative. The data were collected in the form of primary data obtained directly through questionnaires and secondary data obtained through documentation. The populations in this study were all craftsmen of Kemang Langit at Moyo Hilir Sub-District with number of population were 33. The technique used to determine sample in this study was using census sampling technique. The data analysis techniques used were multiple linear regression analysis, t and F statistical tests, and the coefficient of determination (R2). Tests were carried out using the help of the SPSS version 16.0 for windows application. Results of the study showed that the variable of work experience (X1) and work productivity (X2) had a significant influence toward the income of woven cloth craftsmen in the Kemang Langit Group at Moyo Hilir Sub-district, both partially and simultaneously. The ability of work experience variable (X1) and work productivity (X2) in influencing changes in the income of woven cloth craftsmen (Y) in the Kemang Langit woven cloth Group, Samri hamlet, Poto Village, Moyo Hilir Sub-district, was of 46.3%, while the remaining of 53.7% was influenced by other variable outside of this study.